Pengaruh Corporate Social Responsibility terhadap Firm Value pada Perusahaan Manufaktur dan Non Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014 - Amelia Oktrivina DS (STIE Indonesia Banking School, 2016)
The purpose of this study is to examine the effect of Corporate Social Responsibility to Firm Value on the manufacturing and non-manufacturing companies in Indonesia Stock Exchange period 2014. Independent variables used in this study is Corporate Social Responsibility (CSR), while the dependent variable is the Price to Book Value (PBV). The sample in this study consisted of 45 manufacturing companies and 54 non-manufacturing company in Indonesia Stock Exchange in the 2014 study period, that were selected based on certain criteria using purposive sampling method. Analysis of the data used in this research is simple regression analysis. Based on the analysis and discussion of the effect of CSR on firm value, it can put forward some conclusions as follows: 1) CSR significant effect on the Firm Value in manufacturing companies. 2) CSR significant effect on the Firm Value in non-manufacturing company. 3) There is no difference in the effect of CSR on the Firm Value in the manufacturing and non-manufacturing companies. The implication is that companies should be more concern to report their CSR activities because it can influences the firm value